The Book of Job : a biography - Larrimore, Mark J. (Mark Joseph), 1966- (Lives of great religious books., 2013)
Offering rare insights into this iconic and enduring book, Larrimore reveals how Job has come to be viewed as the Bible's answer to the problem of evil and the perennial question of why a God who supposedly loves justice permits bad things to happen to good people.